2021
DOI: 10.1093/ckj/sfab207
|View full text |Cite
|
Sign up to set email alerts
|

Clustering phosphate and iron-related markers and prognosis in dialysis patients

Abstract: Background Hyperphosphatemia in patients undergoing dialysis is common and is associated with mortality. Recently, the link between phosphate metabolism and iron dynamics has received increasing attention. However, the association between this relationship and prognosis remains largely unexplored. Methods We conducted an observational study of patients who initiated dialysis in the 17 centers participating in the Aichi Cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this study, we aimed to reveal the potential of predicting liver‐irAEs occurrence with a combination of some markers by using the GMM, a machine learning model. Currently, machine learning analyses are focused on unsupervised machine learning methods 21–26 . Using a clustering approach, we demonstrated that the objective phenotyping of machines could be stratified by the frequency of liver‐irAEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed to reveal the potential of predicting liver‐irAEs occurrence with a combination of some markers by using the GMM, a machine learning model. Currently, machine learning analyses are focused on unsupervised machine learning methods 21–26 . Using a clustering approach, we demonstrated that the objective phenotyping of machines could be stratified by the frequency of liver‐irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, machine learning analyses are focused on unsupervised machine learning methods. [21][22][23][24][25][26] Using a clustering approach, we demonstrated that the objective phenotyping of machines could be stratified by the frequency of liver-irAEs. We used the GMM because it assumes a multivariate Gaussian distribution for each component.…”
Section: Discussionmentioning
confidence: 99%
“…GMM is a powerful method that was also able to expose potential phenotypes within an observational cohort from a previous report. 37,38 GMM is a powerful tool for phenotyping patients into interpretable groups on a study-by-study basis with different analyses and factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study identified a possible clinical picture that aligns with the picture engaged by clinicians when treating patients. GMM is a powerful method that was also able to expose potential phenotypes within an observational cohort from a previous report 37,38 . GMM is a powerful tool for phenotyping patients into interpretable groups on a study‐by‐study basis with different analyses and factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in CKD patients with or without anemia, iron deficiency on its own is associated with mortality 22 . In addition to the importance of avoiding iron deficiency, observational studies in patients at the induction phase of dialysis suggest that simultaneous management of anemia and iron dynamics, in addition to phosphate management, may lead to a better prognosis 23 . Thus, eliminating iron deficiency is expected to increase life expectancy, either by lowering the risk of anemia, or by lowering the risk of heart failure unrelated to anemia.…”
Section: Discussionmentioning
confidence: 99%